2014
DOI: 10.1016/j.jfda.2014.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the toxic potential of graphene family nanomaterials

Abstract: Graphene, a single-atom-thick carbon nanosheet, has attracted great interest as a promising nanomaterial for a variety of bioapplications because of its extraordinary properties. However, the potential for widespread human exposure raises safety concerns about graphene and its derivatives, referred to as graphene-family nanomaterials. This review summarizes recent findings on the toxicological effects and the potential toxicity mechanisms of graphene-family nanomaterials in bacteria, mammalian cells, and anima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
206
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(215 citation statements)
references
References 96 publications
7
206
0
2
Order By: Relevance
“…Finding an easily accessible, cheap and efficient carrier is one of the most important challenges researchers are facing [11,12]. The carrier system presented here consists of a mixed supramolecular system of CR, which binds TY, which is a strong complexing agent for silver ions, by means of intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…Finding an easily accessible, cheap and efficient carrier is one of the most important challenges researchers are facing [11,12]. The carrier system presented here consists of a mixed supramolecular system of CR, which binds TY, which is a strong complexing agent for silver ions, by means of intercalation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have revealed their different biological properties in invitro and in-vivo conditions, which determine the role and application of nanomaterials (1).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the synthesis of graphene and its derivatives has increased as Graphene Family Nanomaterials (GFNs), including multi-layer and single-layer graphene, graphene nanosheets, ribbon, graphene oxide (GO), and revived graphene oxide (rGO) (1). GO is one of the important derivatives of graphene family whose unique properties such as low toxicity, unique shape and geometry, high biomaterial loading ability, and simple and low-cost synthesis have made it useful in transferring medications, proteins and genes, such that it has been extensively used in pharmaceutical and medical fields in recent years (2).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity and behavior of graphene-based materials in biological systems have been extensively investigated. [37][38][39][40][41][42] Pristine graphene and GO have been found to be toxic to mice in a dose-dependent manner. But functionalized nano-GO (eg, by biocompatible surface coatings) is shown to be much less harmful in both in vitro and in vivo experiments.…”
Section: Biosafety Of Graphene-based Nanosystemsmentioning
confidence: 99%